Introducing facilitated communication training: an action research project - Dearden, Jackie (2005)
Background: Facilitated Communication Training (FCT) is a controversial approach to supporting people with severe communication difficulties. It is one method of supporting Alternative and Augmentative Communication (AAC). It has the potential for enabling people with severe language impairments to access communication aids. The local education authority had experience of enabling a non-verbal young person with cerebral palsy who uses FCT to access mainstream education and were open to exploring whether other young people could benefit from this support.